2018
DOI: 10.1016/j.jcmgh.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a Predictive Molecular Signature for the Onset of NASH-Related Fibrosis in a Translational NASH Mouse Model

Abstract: Background & AimsThe incidence of nonalcoholic steatohepatitis (NASH) is increasing. The pathophysiological mechanisms of NASH and the sequence of events leading to hepatic fibrosis are incompletely understood. The aim of this study was to gain insight into the dynamics of key molecular processes involved in NASH and to rank early markers for hepatic fibrosis.MethodsA time-course study in low-density lipoprotein–receptor knockout. Leiden mice on a high-fat diet was performed to identify the temporal dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 46 publications
4
64
0
Order By: Relevance
“…However, little is known about the effects of OCA at the molecular pathophysiological level, and a detailed investigation of the anti‐inflammatory and anti‐fibrotic effects of OCA has not been performed to date. Here, we investigated the effects of OCA on hepatic inflammatory and profibrotic processes in the HFD‐fed Ldlr‐/‐.Leiden mouse, which recapitulates many phenotypical and molecular facets of NASH in humans . Previously available data on the effects of OCA are based largely on preclinical studies using experimental conditions that appear less relevant to the clinical situation, such as the use of toxic chemicals to induce liver injury or the use of extreme diets (lacking essential amino acids or containing supra‐physiological concentrations of saturated fat, fructose, or cholesterol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the effects of OCA at the molecular pathophysiological level, and a detailed investigation of the anti‐inflammatory and anti‐fibrotic effects of OCA has not been performed to date. Here, we investigated the effects of OCA on hepatic inflammatory and profibrotic processes in the HFD‐fed Ldlr‐/‐.Leiden mouse, which recapitulates many phenotypical and molecular facets of NASH in humans . Previously available data on the effects of OCA are based largely on preclinical studies using experimental conditions that appear less relevant to the clinical situation, such as the use of toxic chemicals to induce liver injury or the use of extreme diets (lacking essential amino acids or containing supra‐physiological concentrations of saturated fat, fructose, or cholesterol).…”
Section: Discussionmentioning
confidence: 99%
“…Herein we describe a preclinical model of NASH in obesity, Ldlr‐/‐.Leiden mice that develop pronounced liver fibrosis in response to energy‐dense high‐fat diets (HFDs) with a macronutrient composition resembling that of human diets (not requiring amino‐acid deficiency or cholesterol supplementation). The model displays phenotypical and metabolic features of high‐risk patients, including insulin resistance . Combined transcriptomics (liver) and metabolomics (serum) profiling revealed that Ldlr‐/‐.Leiden mice recapitulate many of the molecular pathways of human disease including specific fingerprint genes identified in patients with progressive NASH, as well as lipidome/metabolome signatures of NASH patients.…”
mentioning
confidence: 99%
“…In particular, dysregulation of Akr1d1 has been associated with human NAFLD [66], and upregulation of Wwtr1 (also known as TAZ) in human and murine NASH liver [68]. Furthermore, Tead1 has been proposed as a marker of NASH in murine mouse models [69]. Additionally, Vegfa, Lifr, and Nrp1 have been associated with the intrahepatic ligand-receptor signalling network involved in the pathogenesis of NASH [67] ( Fig.…”
Section: Snrna-seq2 Uncovers Transcription Factors and Rate Limiting mentioning
confidence: 99%
“…In all these three cases, the percentage of pathways putatively related to the NAFLD spectrum was estimated by performing a comparison with a pathway consensus list obtained using 19 papers describing transcriptional profiling 6,8,[14][15][16]49,50,[60][61][62][63][64][65][66][67][68][69] or data meta-analysis 7,51 . A further review paper was also added 27 .…”
Section: Microarray Data Analysismentioning
confidence: 99%